Analisis Optimalisasi Kinerja Petugas Apron Movement Control (AMC) dalam Menunjang Keselamatan Operasional di Area Airside Bandar Udara Internasional Sentani Jayapura - Nabila Berliana Nur Azizah; Suprapti Suprapti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Operational safety in the airside area is a crucial aspect of airport operations. The increasing volume of aircraft movements at Sentani International Airport Jayapura requires Apron Movement Control (AMC) personnel to perform their supervisory duties optimally in order to maintain aviation safety, security, and operational efficiency. This study aims to analyze the performance of AMC personnel in supporting operational safety in the airside area, identify the obstacles encountered in carrying out their duties, and examine the factors affecting the optimization of AMC personnel performance. This research employed a descriptive qualitative method. Data were collected through observation, interviews, and documentation. The informants consisted of four AMC personnel, including two Team Leaders (Supervisors) and two AMC Officers at Sentani International Airport Jayapura. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The results indicate that the performance of AMC personnel in supporting operational safety in the airside area has been implemented effectively and in accordance with established Standard Operating Procedures (SOP). AMC personnel carry out apron surveillance, Foreign Object Debris (FOD) control, fuel spill handling, monitoring of aircraft and Ground Support Equipment (GSE) movements, and operational data recording through ATV and Chronos systems effectively. The main challenges faced include limited personnel during peak hours, changing weather conditions, and high operational traffic. Overall, the optimization of AMC personnel performance plays an important role in maintaining safety, security, and smooth airport operations within the airside area of Sentani International Airport Jayapura.